Identification of Work Stress, and Training in Influencing Employee Performance at PT Semen Indonesia Based on Descriptive Statistical Review - Imanda Ratining Putri; Djoko Soelistya (Dinasti Publisher, 2024)
This study aims to identify work stress, training and employee performance at PT Semen Indonesia (Persero) Tbk Gresik in descriptive analysis. This research uses quantitative methods with a descriptive approach. The instrument used in this study was a questionnaire filled out by 142 employees. The questionnaire measured employees' perceptions of work stress and the training they received, as well as an evaluation of their performance. The results showed that the level of employee work stress was in the